Understanding Fiscal Space - Heller, Peter (IMF Policy Discussion Papers; Policy Discussion Paper ;, 2005)
With new initiatives to provide low income countries with external assistance in support of the Millennium Development Goals (MDGs), donors and NGOs are seeking to understand whether "fiscal space" can be provided in the context of IMF-supported programs to support these initiatives. This paper defines the concept of fiscal space and its link to fiscal sustainability, describes alternative ways in which fiscal space can be created, and notes how the IMF can support appropriate efforts to create fiscal space. The paper underscores that the issues that arise in creating fiscal space are not novel, but have always confronted governments in judging whether there is scope for additional expenditure.